(untitled) (Bangladesh Journal of Botany, 2008)
Pollen quantity, viability and germination of four genotypes of Rosa dumalis and R. villosa were investigated. The number of anthers per flower were 90.3 in genotype 4 (Rosa villosa) and 116.4 in genotype 1 (Rosa dumalis). Genotype 1 showed the highest pollen viability on the basis of both TTC and IKI tests. Â Key words: Dogrose, Pollen germination, Pollen viability, Rosa spp. DOI = 10.3329/bjb.v36i2.1511 Bangladesh J. Bot. 36(2): 185-187, 2007 (December)